Professionalism and Popularity in the Digital Age: A Netnographic Study of Teachers' Ethics and Self-Aesthetics as Educational Content Creators on TikTok - Hasnah Faizah; Desi Yusnita Mailinda; Chindy Anjeli; Erma Roza; Asmadi, Asmadi (International Journal of Educational Technology and Society, 2025)
This study examines the phenomenon of creator teachers on TikTok as a form of digital professionalism that represents the integration of ethical values, aesthetics, and educational philosophy. The focus of the research lies in how teachers negotiate moral responsibility and creative expression in the algorithmic culture of social media. The aim of this research is to analyze the philosophical meaning behind teachers' digital representations as well as interpret how moral and aesthetic values are reflected in their pedagogical practices. The method used is digital netnography with four stages: online observation, digital documentation, audience interaction analysis, and researcher reflection. A total of eight teacher accounts were analyzed with a total of 80 videos using a categorization of themes that focused on ethics, aesthetics, and professionalism. The results showed that 62.5% of the content was educational and featured learning innovations, while the other 37.5% contained elements of entertainment and social interaction. High audience interaction shows public appreciation for the creativity and integrity of teachers. Popularity is not solely generated by algorithms, but by the appreciation of moral values and pedagogical beauty in the actions of teachers. Based on the framework of arete and phronesis from Aristotle and the concept of aesthetic experience from Dewey (1934), this study concludes that the digital professionalism of teachers is a form of reflective praxis that combines ethical responsibility and creative expression. This research makes a theoretical contribution by integrating digital netnography and educational philosophy, and shows that teachers in the digital era play the role of moral and creative agents who maintain the dignity of their profession in the algorithmic space.